2008
DOI: 10.1016/j.cmet.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Is a Positive Autocrine Signal for Glucagon Release

Abstract: An important feature of glucose homeostasis is the effective release of glucagon from the pancreatic alpha cell. The molecular mechanisms regulating glucagon secretion are still poorly understood. We now demonstrate that human alpha cells express ionotropic glutamate receptors (iGluRs) that are essential for glucagon release. A lowering in glucose concentration results in the release of glutamate from the alpha cell. Glutamate then acts on iGluRs of the AMPA/kainate type, resulting in membrane depolarization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
189
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(195 citation statements)
references
References 45 publications
5
189
1
Order By: Relevance
“…In contrast, in vivo blockade of AMPA receptors on pancreatic alpha cells induces negative autocrine feedback on glucagon secretion in mice [10]. One possible mechanism behind the surprising increase in glucagon secretion in our study might be that central nervous AMPA blockade by caroverine stimulates autonomic pathways that are known to trigger glucagon release during hypoglycaemia and that such an effect overrode the presumably suppressive effect of systemic AMPA receptor blockade on glucagon secretion.…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, in vivo blockade of AMPA receptors on pancreatic alpha cells induces negative autocrine feedback on glucagon secretion in mice [10]. One possible mechanism behind the surprising increase in glucagon secretion in our study might be that central nervous AMPA blockade by caroverine stimulates autonomic pathways that are known to trigger glucagon release during hypoglycaemia and that such an effect overrode the presumably suppressive effect of systemic AMPA receptor blockade on glucagon secretion.…”
Section: Discussioncontrasting
confidence: 63%
“…Glucagon, the functional homolog of AKH in mammals, autoregulates its own production via proliferation control of the pancreatic alpha cells (Gelling et al 2003) and via regulation of their secretory activity (Ma et al 2005;Cabrera et al 2008). Our data show that unlike its mammalian homolog, AKH does not affect the number of CC cells.…”
Section: Autoregulation Of the Akh Genementioning
confidence: 54%
“…It is known that paracrine factors including insulin, zinc and GABA play important roles in modulating glucose-regulated glucagon secretion [39]. A recent study suggested that glutamate released from alpha cells exerts autocrine effects to produce adequate glucagon release under hypoglycaemic conditions [40]. Given that, physiologically, a negative feedback simultaneously occurs during a secretory process, it is possible that the HCN channel in alpha cells may function as a negative feedback modulator to prevent an 'overshooting' of glucagon secretion under glucagon-stimulatory conditions, hence to maintain the hormone at appropriate levels.…”
Section: Discussionmentioning
confidence: 99%